Analisis Kompetensi, Produktivitas Kerja, dan Kinerja Pegawai pada Pusat Pengelolaan Pendapatan Daerah Wilayah Karawang - Lilis Fitriyani; Aji Tuhagana; Zenita Apriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out and understand the results of competency analysis, work productivity and employee performance at the P3DW Karawang Office. This research uses qualitative methods with a descriptive approach, and data is collected through interviews, observation and documentation. The research results show that employee competency at the P3DW Karawang Office is good, but special training and providing equal development opportunities for all employees are still needed to improve their skills. Employee work productivity is considered quite good, supported by effective communication and cooperation with superiors. However, this research also found that several facilities and infrastructure in the office were still inadequate. Therefore, it is necessary to make efforts to improve facilities and develop human resources more intensively to ensure employee performance can continue to improve and support the achievement of organizational goals..